Regulatory Sandboxes as Catalysts for Fintech Innovation: Evaluating the Impact on Start-Up Success and Policy Evolution - Dewi Puspita Sari; Alfina Dwi Yanti (Start-up and Financial Technology, 2025)
Objective: Regulatory sandboxes have become a global instrument for managing the complexity of FinTech innovation while maintaining regulatory stability. This study aims to comprehensively evaluate regulatory sandboxes as a crucial policy innovation instrument in the FinTech landscape. Research Design & Methods: This study adopts a qualitative methodology, combining an extensive literature review and comparative case studies. Data was collected from various sources, including legal documents, regulations from the OJK and Bank Indonesia in Indonesia, reports from global authorities such as the UK's FCA, and academic journal articles. Findings: The study's results show that sandboxes are significantly positively correlated with the success of FinTech startups. Participation in sandboxes is associated with a 15% increase in capital raised and a 50% higher probability of fundraising. These benefits arise through reduced information asymmetry and regulatory costs, which particularly help smaller and younger companies. Additionally, sandboxes facilitate critical two-way dialogue between innovators and regulators, accelerate time to market, encourage competition, and contribute to banking stability.Implications & Recommendations: Research confirms that sandboxes are valuable but not a silver bullet. The effectiveness of sandboxes depends on strategic design, resource support, and regulatory integration. Therefore, regulators need to encourage the adoption of adaptive regulatory approaches, adequate funding, and cross-jurisdictional cooperation. Contribution & Value Added: This study presents a holistic evaluation that affirms the benefits while critiquing the limitations of sandboxes. It combines a global perspective and analysis of Indonesian regulations to provide evidence-based insights and practical recommendations for optimizing sandboxes as responsible and sustainable innovation drivers.